Silane coupling agent
Patent Information
- Application Number
- KR1020237008971
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-20
- Filing Date
- 2021-08-05
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-08-05
Smart Images

Figure 112023029259545-PCT00020_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to a silane coupling agent that has excellent storage stability and an excellent effect of improving the adhesion between inorganic and organic materials. The present application claims priority to Japanese Patent Application No. 2020-139427 filed on August 20, 2020, and incorporates the contents thereof herein by reference. Background Technology
[0002] Conventionally, compounds that act to firmly link inorganic and organic materials having different chemical properties, such as compounds having a reactive group with organic materials and a silanol group that forms a chemical bond with the surface of inorganic materials (=silanol compounds), or oligomers thereof, are known.
[0003] The above silanol compound or its oligomer is used as a surface modifier or primer for inorganic substrates. For example, in the WOW (Wafer On Wafer) method for stacking multiple wafers with circuits, the COW (Chip On Wafer) method for stacking multiple chips on a wafer with circuits, and the COC (Chip On Chip) method for stacking multiple chips, both the stacking side and the stacking side are subjected to a modification treatment using a silanol compound or its oligomer, and then bonded with a permanent adhesive.
[0004] However, the problem was that silanol compounds or their oligomers have low storage stability and are prone to gelation due to dehydration condensation reactions because they have highly reactive silanol groups.
[0005] Patent Document 1 describes a composition containing a silane oligomer obtained by hydrolyzing and condensing a silane compound having a reactive functional group such as 3-glycidoxypropyltrimethoxysilane and three hydrolyzable groups, a hydrolyzed polycondensate of tetramethoxysilane, and an alcohol having 1 to 6 carbon atoms, which has excellent storage stability. However, the viscosity is too high for use in coating a substrate (particularly thin substrates such as wafers or chips) to modify the surface, so it was necessary to dilute it by adding water and / or alcohol each time. In addition, the problem was that the concentration of silanol groups contributing to the expression of adhesion was low, so sufficient adhesion was not obtained when diluted to the extent that good coating properties were obtained. Prior art literature
[0006] Patent Document 1: Japanese Published Patent No. (Hei) 10-251516 The problem to be solved
[0007] Accordingly, the object of the present disclosure is to provide a silane coupling agent that has low viscosity, excellent coating properties, and the effect of firmly bonding inorganic and organic materials.
[0008] Another objective of the present disclosure is to provide a silane coupling agent having excellent coating properties and storage stability, and having the effect of firmly bonding inorganic and organic materials.
[0009] Another objective of the present disclosure is to provide an adhesive comprising the silane coupling agent and a curable compound, which has excellent adhesion and storage stability.
[0010] Another object of the present disclosure is to provide a three-dimensional laminate formed by stacking wafers and / or chips using the adhesive.
[0011] Another objective of the present disclosure is to provide a semiconductor device having the above-described three-dimensional stack. means of solving the problem
[0012] As a result of careful consideration to solve the above problem, the inventors discovered that when an alkoxysilane is hydrolyzed under acidic conditions, in the absence of an organic solvent, or even if an organic solvent is present, in a condition where the organic solvent content is 0.7 parts by weight or less per 1 part by weight of the compound represented by Formula (2) below, the hydrolysis and dehydration condensation reaction can be promoted while suppressing gelation, thereby obtaining a silane coupling agent containing a polycondensate with a high silanol group concentration in a specific ratio, the silane coupling agent has the effect of firmly adhering to inorganic and organic materials, and when the silane coupling agent is diluted with a specific solvent, the adhesion between inorganic and organic materials can be maintained at a high level while increasing storage stability or coating properties. The present disclosure is completed based on these findings.
[0013] That is, the present disclosure provides a silane coupling agent containing the following silicon compound and water, wherein the concentration of the silicon compound is 0.01 to 10 weight%.
[0014] Silicon compound: comprises a compound (I) represented by the following formula (1) and a polycondensate thereof, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0015] [Painting 1]
[0016]
[0017] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter.)
[0018] The present disclosure also provides the silane coupling agent having a pH of 4 or less.
[0019] The present disclosure also provides the silane coupling agent containing a solvent having the following characteristics.
[0020] Solvent: The evaporation rate of butyl acetate is 10 to 400 when the evaporation rate of butyl acetate is set to 100.
[0021] The present disclosure also provides the silane coupling agent containing a solvent having additionally the following characteristics.
[0022] Solvent: The evaporation rate is 10 to 400 when the evaporation rate of butyl acetate is set to 100, and the SP value at 25℃ is 6 to 15.
[0023] The present disclosure also provides the silane coupling agent which is a surface modifier.
[0024] The present disclosure also relates to a condition in which, under conditions of pH 4 or lower, an organic solvent is absent, or even if an organic solvent is present, the organic solvent content is 0.7 parts by weight or less per 1 part by weight of a compound represented by the following formula (2), the following formula (2)
[0025] [Painting 2]
[0026]
[0027] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter, and OR 1 ~OR 3 It is identical or different and exhibits a hydrolytic group)
[0028] Hydrolyze the compound represented by, the following formula (1)
[0029] [Tuesday 3]
[0030]
[0031] (In the formula, Y is the same as above)
[0032] A method for manufacturing a silane coupling agent is provided, comprising a process of obtaining a compound represented by the formula (1), and a process of obtaining the silane coupling agent by applying the obtained compound represented by the formula (1) to a polycondensation reaction.
[0033] The present disclosure also provides an adhesive comprising the following silicon compound and a curable compound.
[0034] Silicon compound: comprises a compound (I) represented by the following formula (1) and a polycondensate thereof, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) in the standard polystyrene equivalent [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0035] [Painting 4]
[0036]
[0037] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter.)
[0038] The present disclosure also provides the adhesive in which the content of the silicon compound is 0.01 to 40 parts by weight per 100 parts by weight of the curable compound.
[0039] The present disclosure also provides a three-dimensional laminate having a configuration in which wafers and wafers, chips and chips, or wafers and chips are laminated through the adhesive.
[0040] The present disclosure also provides a semiconductor device having the three-dimensional stack. Effects of the invention
[0041] The silane coupling agent of the present disclosure has a high concentration of silanol groups, so it can firmly bond inorganic and organic materials even at low concentrations. In addition, it has excellent storage stability, so it can suppress gelation over a long period of time.
[0042] In addition, when using an adhesive obtained by combining a curable compound with the silane coupling agent of the present disclosure, although it was conventionally necessary to apply the adhesive to both sides of the bonding surface of the substrate, it is possible to firmly bond and fix the substrate by applying it to only one side and then bonding it, thereby providing excellent workability.
[0043] When the above silane coupling agent or adhesive is used in semiconductor chip stacking technologies such as WOW (Wafer on Wafer), COW (Chip on Wafer), or COC (Chip on Chip), extremely fine and thin wafers or chips can be efficiently stacked and strongly bonded, thereby enabling the manufacture of a three-dimensional stack with high yield. Brief explanation of the drawing
[0044] Figure 1 is a diagram showing the effect of pH on the conversion rate in hydrolysis and polycondensation reactions under conditions of a temperature of 50°C and 6 eq of water. Figure 2 is a diagram showing the effect of reaction temperature on the conversion rate in hydrolysis and polycondensation reactions under conditions of pH 4 and water 6 eq. Figure 3 is a diagram showing the effect of the amount of water on the conversion rate in hydrolysis and polycondensation reactions under conditions of pH 4 and a temperature of 70°C. FIG. 4 is a diagram showing the Si-NMR measurement results (A) of the silane coupling agent obtained in Example 1 and the Si-NMR measurement results (B) of the silane coupling agent obtained in Comparative Example 2. Figure 5 is a diagram showing the storage stability of the silane coupling agent (+ethanol) obtained in Example 1 and the silane coupling agent (+PGMEA) obtained in Example 2 at 5°C and 40°C. Specific details for implementing the invention
[0045] [Silanic Coupling Agents]
[0046] The silane coupling agent of the present disclosure contains the following silicon compound and water, and the concentration of the silicon compound is 0.01 to 10 weight%.
[0047] Silicon compound: Compound (I) and its polycondensate, wherein the ratio of the content of compound (I) and the polycondensate of compound (I) to the content of compound (II) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5. Additionally, compound (I) is a compound represented by the following formula (1).
[0048] [Tuesday 5]
[0049]
[0050] In the above formula (1), Y represents a hydrocarbon group having 1 to 10 carbon atoms that includes a reactive group with organic matter.
[0051] The reactive groups with the organic material include addition reactive groups, substitution reactive groups, or polymerization reactive groups (radical polymerization reactive groups or cationic polymerization reactive groups) with the organic material, and examples include amino groups, epoxy groups, (meth)acryloyloxy groups, vinyl groups, mercapto groups, isocyanurate groups, etc. When the silane coupling agent of the present disclosure is used for the purpose of improving the adhesion between an inorganic material (e.g., silicon wafer, glass, etc.) and an adhesive, for example, when bonding an inorganic material using an adhesive, it is preferable that the reactive groups with the organic material be groups that have excellent reactivity with the adhesive; if the adhesive contains an epoxy resin as a curable compound, an epoxy group is preferred, and if the adhesive uses an acrylic resin as a curable compound, a (meth)acryloyloxy group is preferred.
[0052] The above epoxy group includes groups represented by the following formulas (e-1) to (e-3). In addition, R in the following formulas is a hydrogen atom or C 1-3 It represents an alkyl group.
[0053] [Tuesday 6]
[0054]
[0055] The above hydrocarbon groups include aliphatic hydrocarbon groups, alicyclic hydrocarbon groups, aromatic hydrocarbon groups, and groups combined thereof.
[0056] Examples of aliphatic hydrocarbon groups include alkyl groups having 1 to 10 carbon atoms (preferably 1 to 3), such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, s-butyl, t-butyl, pentyl, hexyl, and decyl groups; alkenyl groups having 2 to 10 carbon atoms (preferably 2 to 3), such as vinyl, allyl, and 1-butenyl groups; and alkynyl groups having 2 to 10 carbon atoms (preferably 2 to 3), such as ethinyl and propynyl groups.
[0057] As a cycloaliphatic hydrocarbon group, C 3-10 A cycloalkyl group having about 3 to 10 (preferably 5 to 8) members, such as a cyclopropyl group, cyclobutyl group, cyclopentyl group, cyclohexyl group, cyclooctyl group; about 3 to 10 (preferably 5 to 8) members, such as a cyclopentenyl group, cyclohexenyl group; perhydronaphthalene-1-yl group, norbornyl group, adamantyl group, tricyclo[5.2.1.0 2,6 Examples include decane-8-yl groups and other exchangeable hydrocarbon groups.
[0058] As an aromatic hydrocarbon group, C 6-10 Aromatic hydrocarbon groups are preferred, such as phenyl groups, naphthyl groups, etc.
[0059] The polycondensate of compound (I) is a resin (oligomer or polymer) having a siloxane (Si-O-Si) backbone. Examples of the structures of the resin include cyclic, chain (straight chain, branched chain), basket, ladder, etc.
[0060] Among the above polycondensates, it is preferable to have a chain-like (particularly linear) structure, as it has excellent solvent solubility and can be applied by spin coating or the like when used for the purpose of modifying the surface of a substrate, and a compound represented by the following formula (3) is particularly preferred. In the following formula, Y is the same as above. n is the number of repeating units appearing in parentheses and represents an integer of 1 or more. In addition, n+1 Ys may be the same or different.
[0061] [Tuesday 7]
[0062]
[0063] The above silane coupling agent is a silicon compound and contains compound (I) and compound (II), which has a weight average molecular weight of 200 to 10000 in the standard polystyrene equivalent among the polycondensation compounds of compound (I) (preferably, the compound represented by formula (3) above).
[0064] The ratio of the content of the above compound (I) and compound (II) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5, and the lower limit is preferably 3 / 97, more preferably 5 / 95, particularly preferably 10 / 90, and most preferably 20 / 80 in terms of inhibiting gel formation. In addition, the upper limit is preferably 93 / 7, particularly preferably 90 / 10 in terms of improving adhesion.
[0065] If the content of compound (I) exceeds the above range (in other words, if the content of compound (II) falls below the above range), the adhesiveness tends to decrease, and if the content of compound (II) exceeds the above range (i.e., if the content of compound (I) falls below the above range), gelation tends to occur easily.
[0066] The weight average molecular weight of the silicon compound included in the above silane coupling agent, calculated by standard polystyrene conversion, is, for example, 150 to 9500. The lower limit is preferably 200, more preferably 230, and particularly preferably 250. In addition, the upper limit is preferably 8000, more preferably 7000, more preferably 5000, even more preferably 2000, even more preferably 1000, particularly preferably 800, most preferably 600, and particularly preferably 550, in that the silanol group concentration is high and can exhibit an effect of improving adhesion between inorganic and organic materials at lower concentrations. Furthermore, the molecular weight distribution (Mw / Mn) of the silicon compound is, for example, 1.1 to 4.0, preferably 1.1 to 2.0, and particularly preferably 1.1 to 1.5.
[0067] The silane coupling agent of the present disclosure may contain silicon compounds having structures other than those of compounds (I) and (II) as silicon compounds, for example, together with compound (I) (=trisilanol), may contain disilanol represented by the following formula (1') or monosilanol represented by the following formula (1"). Y in the following formula is the same as above.
[0068] [Tue 8]
[0069]
[0070] Among the above formulas, OR 1 , OR 2 is identical or different and represents a hydrolytic group. As the hydrolytic group, for example, C 1-5 Alkoxy group, C 1-5 Examples include acyloxy groups, etc. Therefore, R 1 , R 2 is, for example, the same or different, and C 1-5 alkyl group or C 1-5 It is Asilgi.
[0071] In addition, together with compound (II), it may contain a compound (=compound (II')) which is a polycondensate of compound (I) and has a weight average molecular weight in standard polystyrene conversion that is less than the lower limit of the weight average molecular weight of compound (II) (e.g., 200) or a compound (=compound (II")) which has an upper limit of the weight average molecular weight of compound (II) (e.g., 10000). However, considering the high concentration of silanol groups, the ability to improve adhesion between inorganic and organic materials at lower concentrations, and excellent storage stability, the total content of compound (II') and compound (II") is preferably 30% by weight or less of the total silicon compounds included in the silane coupling agent, more preferably 20% by weight or less, particularly preferably 10% by weight or less, most preferably 5% by weight or less, and particularly preferably 1% by weight or less.
[0072] In addition, the silane coupling agent of the present disclosure may include a compound represented by the following formula (2) (for example, may remain unhydrolyzed). In order to exhibit an effect of improving adhesion between inorganic and organic materials at low concentrations, the content of the compound represented by the following formula (2) is preferably 50% by weight or less of the total silicon compound included in the silane coupling agent, more preferably 40% by weight or less, particularly preferably 30% by weight or less, and most preferably 25% by weight or less. Y and R in the following formula 1 , R 2 It is the same as above.
[0073] [Tue 9]
[0074]
[0075] Among the above formulas, OR 3 represents a hydrolytic group. As the hydrolytic group, for example, C 1-5 Alkoxy group, C 1-5 Examples include acyloxy groups, etc. Therefore, R3 Eun, for example, is the same or different, and C 1-5 alkyl group or C 1-5 It is Asilgi.
[0076] It is preferable that the above silane coupling agent be acidic for excellent storage stability, and the pH of the silane coupling agent is preferably, for example, 4 or lower (i.e., pH is 4 or more acidic than 4), more preferably 2 to 4, and particularly preferably 3 to 4. If the pH of the above silane coupling agent deviates from the above range toward the basic side, the dehydration condensation reaction of the silicon compound in the silane coupling agent proceeds and gels, so it is not desirable because it becomes difficult to apply by spin coating or the like when used for the purpose of modifying the surface of a substrate, etc. On the other hand, if the pH of the above silane coupling agent deviates from the above range toward the acidic side, the reactive group becomes prone to decomposition, so it is not desirable.
[0077] The viscosity of the above silane coupling agent is preferably about 1 to 300 mPa·s in order to provide good applicability. The above viscosity can be measured, for example, using a digital viscometer (model number “DVU-EII type”, manufactured by TOKIMEC INC.) under conditions of rotor: standard 1°34’×R24, temperature: 25℃, and rotation speed: 0.5 to 10 rpm.
[0078] The above silane coupling agent may use water or a solvent as a diluent. As the solvent, it is preferable to use a solvent that is easily volatile. A silane coupling agent containing a solvent can be applied thickly because the fluidity is reduced as the solvent evaporates rapidly after application, and the concentration of silanol groups in the coating film can be increased, thereby enhancing the effect of improving adhesion between inorganic and organic materials.
[0079] As for the above solvent, when the evaporation rate of butyl acetate under a specific temperature and pressure is set to 100, a solvent having an evaporation rate of, for example, 10 to 400 under the same temperature and pressure is preferred. Furthermore, in order to obtain the effect of improving storage stability, the lower limit of the evaporation rate is more preferably 20, particularly preferably 50, most preferably 100, and particularly preferably 150, and the upper limit of the evaporation rate is more preferably 350, particularly preferably 300, and most preferably 250. In addition, the evaporation rate of the above solvent is, for example, the evaporation rate at room temperature (preferably 25°C) and atmospheric pressure.
[0080] In addition, as the above solvent, it is preferable to use a solvent having an SP value (by Fedors method) of 6 to 15 (more preferably 9 to 15, particularly preferably 9 to 14, most preferably 10 to 13) at 25°C, in that the solvent caps the silanol group and inhibits the progress of the dehydration condensation reaction of the silicon compound, thereby obtaining the effect of further improving storage stability.
[0081] In particular, regarding the above solvent, it is desirable to use a solvent in which the evaporation rate when the evaporation rate of butyl acetate is set to 100 is within the above range, and the SP value at 25°C is within the above range, in order to increase both the adhesion and preservation stability of inorganic and organic materials.
[0082] Examples of the above solvents include aliphatic alcohols such as ethanol, 1-propanol, 1-butanol, and 1-pentanol; glycol ether esters such as propylene glycol methyl ether acetate (PGMEA). These may be used individually or in combination of two or more.
[0083] Among the above solvents, aliphatic alcohols are preferred in that they offer excellent workability and handling properties during application, as well as enhanced adhesion between inorganic and organic materials and improved storage stability; particularly preferably, monovalent aliphatic alcohols, and particularly preferably monovalent C 2-6 It is an aliphatic alcohol, particularly preferably ethanol.
[0084] The above silane coupling agent has excellent storage stability, and the increase in weight average molecular weight when stored at 5°C for 30 days is, for example, 500 or less, preferably 200 or less, particularly preferably 100 or less, most preferably 50 or less.
[0085] The above silane coupling agent has excellent storage stability even in high-temperature environments, and the increase in weight-average molecular weight when stored at 40°C for 30 days is, for example, 2000 or less, preferably 1500 or less, particularly preferably 1000 or less, and most preferably 700 or less.
[0086] The silane coupling agent of the present disclosure has low viscosity and excellent applicability. In addition, it has the effect of improving the adhesion between inorganic and organic materials. Therefore, by applying the silane coupling agent to the surface of an inorganic material (e.g., silicon wafer, glass, etc.), the adhesion with an organic adhesive is improved. Consequently, the silane coupling agent can be very suitablely used as a surface modifier for inorganic materials.
[0087] [Method for manufacturing silane coupling agents]
[0088] The above silane coupling agent can be manufactured through the following processes [I] and [II].
[0089] Process [I]: under conditions of pH 4 or lower, and at the same time, in the absence of an organic solvent, or even if an organic solvent is present, in the case where the organic solvent content is 0.7 parts by weight or less per 1 part by weight of the compound represented by the following formula (2), the following formula (2)
[0090] [Tuesday 10]
[0091]
[0092] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter, and OR 1 ~OR 3 It is identical or different and exhibits a hydrolytic group)
[0093] Hydrolyze the compound represented by, the following formula (1)
[0094] [Tuesday 11]
[0095]
[0096] (In the formula, Y is the same as above)
[0097] A process for obtaining a compound represented by .
[0098] Process [II]: A process of adding the compound represented by Formula (1) obtained through the above process to a polycondensation reaction.
[0099] The above processes [I] and [II] are described in detail below.
[0100] [Tuesday 12]
[0101]
[0102] Among the above formulas, R 1 , R 2 , R 3 , Y, and n are the same as above.
[0103] Examples of compounds represented by formula (2), wherein Y in the formula is a hydrocarbon group having 1 to 10 carbon atoms containing an epoxy group, include 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyldimethoxysilane, 3-glycidoxypropyl methyldiethoxysilane, and 3-glycidoxypropyl triethoxysilane.
[0104] Examples of compounds represented by formula (2), wherein Y in the formula is a hydrocarbon group having 1 to 10 carbon atoms containing a (meth)acryloyloxy group, include 3-(meth)acryloyloxypropylmethyldimethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropylmethyldiethoxysilane, and 3-(meth)acryloyloxypropyltriethoxysilane.
[0105] The above process [I] is a process of obtaining a compound represented by formula (1) by performing a hydrolysis reaction of a compound represented by formula (2). The amount of water used is, for example, 0.6 to 12 moles per mole of the compound represented by formula (2).
[0106] The above hydrolysis reaction is carried out under conditions of pH 4 or lower (preferably pH 2 to 4, particularly preferably pH 3 to 4).
[0107] In addition, the above hydrolysis reaction is carried out under conditions where there is no organic solvent, or where there is an organic solvent, the organic solvent content is 0.7 parts by weight or less per 1 part by weight of the compound represented by the following formula (2).
[0108] Examples of the above organic solvents include monovalent aliphatic alcohols such as ethanol, 1-propanol, 1-butanol, and 1-pentanol; and polar organic solvents such as glycol ether esters such as propylene glycol methyl ether acetate.
[0109] The upper limit of the content of the above organic solvent (the total amount if two or more types are contained) is 0.7 parts by weight per 1 part by weight of the compound represented by the above formula (2), preferably 0.5 parts by weight, particularly preferably 0.3 parts by weight, and particularly preferably 0.2 parts by weight.
[0110] Since the above hydrolysis reaction is carried out under the above conditions, the progress of the hydrolysis reaction of the compound represented by Equation (2) is promoted, which can increase the amount of silanol groups generated and efficiently produce the compound represented by Equation (1).
[0111] If an organic solvent (especially the polar organic solvent) is present in the reaction system during the hydrolysis reaction in excess of the above range, the progress of the hydrolysis reaction of the compound represented by Equation (2) is inhibited, making it difficult to efficiently produce the compound represented by Equation (1).
[0112] In addition, if the pH in the reaction system during the hydrolysis reaction exceeds 4 and shifts toward the alkaline side, the progress of the hydrolysis reaction of the compound represented by Equation (2) is inhibited, thereby reducing the yield of compound (II) and increasing the byproduct rate of compound (II') or compound (II"). As a result, the formation of a three-dimensional cross-linked structure proceeds, and there is a tendency for it to become gelled. On the other hand, if the pH is lowered excessively, the reactive group tends to decompose easily.
[0113] The above process [II] is a process of dehydrating and condensing the compound represented by formula (1) obtained through the above process [I] to obtain the compound represented by formula (3), which is obtained by dehydrating and condensing (n+1) of the compounds represented by formula (1).
[0114] When a compound represented by formula (1) is applied to a dehydration condensation reaction under conditions of pH 4 or lower (preferably pH 2 to 4, particularly preferably pH 3 to 4), a reaction forming a two-dimensional network proceeds selectively rather than a reaction forming a three-dimensional cross-linked structure. As a result, a silane coupling agent is obtained that suppresses gelation, increases the production rate of compound (II), is easy to apply by spin coating or the like, and has excellent adhesion between inorganic and organic materials.
[0115] In addition, the above dehydration condensation reaction may be carried out in the presence of an organic solvent, but, for example, the reactions of process [I] and process [II] may be carried out in one pot, and process [II] may be carried out under the same conditions as process [I], that is, in the absence of an organic solvent, or even if an organic solvent is present, under conditions where the content of the organic solvent is 0.7 parts by weight or less per 1 part by weight of the compound represented by the following formula (2).
[0116] The reaction atmosphere of the above processes [I] and [II] is not particularly limited as long as it does not inhibit the reaction, and may be any of the following:, for example, an air atmosphere, a nitrogen atmosphere, an argon atmosphere.
[0117] The reaction temperature of the above processes [I] and [II] is, for example, about 40 to 85°C. The reaction time is, for example, about 20 hours or less. In addition, the reaction can be carried out in any method such as batch, semi-batch, or continuous. The progress of the dehydration condensation reaction can be stopped by lowering the temperature in the reaction system to 30°C or lower. Alternatively, the dehydration condensation reaction can be stopped by adding one or more types of solvents to lower the concentration in the reaction system.
[0118] Examples of the above solvents include those that can be used as diluents for silane coupling agents.
[0119] After the reaction of the above process [II] is finished, the reaction product obtained can be separated and purified by separation means such as filtration, concentration, distillation, extraction, crystallization, adsorption, recrystallization, column chromatography, etc., or by a combination of these separation means.
[0120] [Adhesive]
[0121] The adhesive of the present disclosure comprises the following silicon compound and a curable compound.
[0122] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0123] The above silicon compound is the same as the silicon compound included in the silane coupling agent described above.
[0124] The above-mentioned curable compound includes a thermoplastic resin or a thermo(or photo)curable resin. The above-mentioned curable compound can be appropriately selected and used depending on the application. For example, it is preferable to use a thermo(or photo)curable resin for applications involving the manufacture of a three-dimensional laminate formed by stacking wafers and wafers, chips and chips, or wafers and chips.
[0125] A heat (or light)curable resin is a compound in which curing proceeds irreversibly by heating (or light irradiation), and includes, for example, epoxy resins and acrylic resins. These may be used individually or in combination of two or more types.
[0126] As an epoxy resin, for example, a compound containing an alicyclic epoxy group (a group represented by formula (e-1) described above), such as 3,4-epoxycyclohexylmethyl(3,4-epoxy)cyclohexane carboxylate, (3,4,3',4'-diepoxy)bicyclohexyl, bis(3,4-epoxycyclohexylmethyl) ether, 1,2-epoxy-1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, 2,2-bis(3,4-epoxycyclohexane-1-yl)propane, 1,2-bis(3,4-epoxycyclohexane-1-yl)ethane; Examples include alicyclic glycidyl ethers such as hydrogenated bisphenol A type diglycidyl ether, hydrogenated bisphenol F type diglycidyl ether, hydrogenated biphenol type diglycidyl ether, hydrogenated phenol novolak type diglycidyl ether, hydrogenated cresol novolak type diglycidyl ether; aromatic glycidyl ethers such as bisphenol A type diglycidyl ether, bisphenol F type diglycidyl ether, biphenol type diglycidyl ether, phenol novolak type diglycidyl ether, cresol novolak type diglycidyl ether, etc., which contain a glycidyl ether group (a group represented by formula (e-3) described above).
[0127] The above epoxy resin includes, in addition to the above compounds, polyorganosilsesquioxanes containing epoxy groups. Furthermore, the above epoxy groups include groups represented by formulas (e-1) to (e-3) described above.
[0128] Epoxy group-containing polyorganosilsesquioxane is a compound having a main chain backbone formed by siloxane bonds and a group including an epoxy group that is bonded to the main chain backbone.
[0129] Epoxy group-containing polyorganosilsesquioxanes include those having various structures such as ladder-type structures, complete basket-type structures, incomplete basket-type structures, and random-type structures; among these, silsesquioxanes having an incomplete basket-type structure are preferred in that they can form a cured product having high hardness.
[0130] The above-mentioned epoxy group-containing polyorganosilsesquioxane having an incomplete basket-type structure is of the following formula (S1)
[0131] [R a SiO 3 / 2 ] (S1)
[0132] [Equation (S1), R a [ represents a group containing an epoxy group, an aryl group, an aralkyl group, a cycloalkyl group, an alkyl group, an alkenyl group, or a hydrogen atom]
[0133] The constituent unit indicated by, and the following formula (S2)
[0134] [R a SiO 2 / 2 (OR b )] (S2)
[0135] [Equation (S2), R a is the same as above. R b represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0136] Includes constituent units indicated by,
[0137] In the total amount of the constituent unit represented by the above formula (S1) and the constituent unit represented by the above formula (S2), at least one is R a It is a constituent unit containing an epoxy group.
[0138] The constituent unit represented by the above equation (S1) is called the T3 body. Also, the constituent unit represented by the above equation (S2) is called the T2 body. All of these constituent units are T units.
[0139] Examples of the above aryl groups include aryl groups having 6 to 10 carbon atoms, such as phenyl groups and naphthyl groups.
[0140] Examples of the above aralkyl groups include aralkyl groups having 7 to 12 carbon atoms, such as benzyl groups and phenethyl groups.
[0141] Examples of the above cycloalkyl groups include cycloalkyl groups having 3 to 6 carbon atoms, such as cyclobutyl groups, cyclopentyl groups, and cyclohexyl groups.
[0142] Examples of the above alkyl groups include straight-chain or branched-chain alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, propyl, n-butyl, isopropyl, isobutyl, s-butyl, t-butyl, and isopentyl groups.
[0143] Examples of the above alkenyl groups include straight or branched alkenyl groups having 2 to 6 carbon atoms, such as vinyl groups, allyl groups, and isopropenyl groups.
[0144] Examples of the above carbon 1 to 4 alkoxy groups include methoxy groups, ethoxy groups, propoxy groups, isopropyloxy groups, butoxy groups, isobutyloxy groups, etc.
[0145] The above epoxy group-containing polyorganosilsesquioxane is a constituent unit represented by the above formula (S1) or (S2), and R in the formula a A is a constituent unit represented by the above formula (S1) or (S2), together with a constituent unit containing an epoxy group, and R in the formula a It may also contain a constituent unit that is a substituted or unsubstituted aryl group (e.g., a phenyl group).
[0146] The above T3 / T2 body / molar ratio, that is, the ratio of the content of the constituent unit represented by Equation (S1) and the constituent unit represented by Equation (S2) (former / latter; molar ratio), is, for example, 5 to 500. The lower limit of the molar ratio is preferably 7, particularly preferably 8, most preferably 9, and particularly 10, in order to obtain the effect of improving the hardness and scratch resistance of the obtained cured product. The upper limit of the molar ratio is preferably 50, particularly preferably 30, most preferably 20, and particularly 15. The molar ratio is, for example, 29 It can be obtained by measuring the Si-NMR spectrum. 29In the Si-NMR spectrum, since silicon atoms in the T3 body and silicon atoms in the T2 body have peaks at different positions, the molar ratio is obtained by calculating the ratio of the integral values of each peak.
[0147] In addition, 29 Si-NMR spectrum measurements can be performed using the following apparatus and conditions.
[0148] Measuring device: Product name "JNM-ECA500NMR", manufactured by Nihon Denshi Kabushiki Kaisha (JEOL Ltd.)
[0149] Solvent: Deuterium chloroform
[0150] Accumulated count: 1,800 times
[0151] Measured temperature: 25℃
[0152] The monomer components constituting the acrylic resin include (meth)acrylate alkyl esters and functional group-containing monomers. The monomer components may also include one or more monomers copolymerizable with (meth)acrylate alkyl esters or functional group-containing monomers.
[0153] Examples of the above (meth)acrylate alkyl esters include (meth)acrylate alkyl esters having 1 to 20 carbon atoms in the alkyl group, such as (meth)acrylate ethyl, (meth)acrylate butyl, (meth)acrylate 2-ethylhexyl, and (meth)acrylate isononyl.
[0154] Examples of the above functional group-containing monomers include, for instance, carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, fumaric acid, or their anhydrides; hydroxyl group-containing monomers such as (meth)acrylic acid hydroxyethyl; epoxy group-containing monomers such as (meth)acrylic acid glycidyl, (meth)acrylic acid methylglycidyl; cyano group-containing monomers such as (meth)acrylonitrile; and amide group-containing monomers such as N-hydroxyethylacrylamide.
[0155] In addition to the silicon compound and the curable compound, the adhesive of the present disclosure may contain one or more other components to a extent that does not impair the properties of the present disclosure. Examples of other components include cationic polymerization initiators, crosslinking agents, crosslinking accelerators, tackifiers (e.g., rosin derivative resins, polyterpene resins, petroleum resins, oil-soluble phenolic resins, etc.), anti-aging agents, fillers, UV absorbers, antioxidants, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, water, solvents, fillers, etc. Examples of the solvents may include the same as the solvents that may contain the silane coupling agent described above.
[0156] When the above adhesive contains an epoxy resin as a curable compound, it is preferable to additionally contain a cationic polymerization initiator.
[0157] The above cationic polymerization initiator includes a photo or thermal cationic polymerization initiator.
[0158] As the above-mentioned cationic polymerization initiator, for example, PF6 having a sulfonium ion or an iodine ion as the cation part. - , S b F6 - Examples include onium salts in which the back is the anion part.
[0159] The amount of cationic polymerization initiator used is, for example, 0.1 to 20 parts by weight per 100 parts by weight of the epoxy compound.
[0160] When the above adhesive contains acrylic resin as a curable compound, it is preferable to additionally contain a crosslinking agent.
[0161] As the above-mentioned crosslinking agent, isocyanate-based crosslinking agents such as 1,6-hexamethylene diisocyanate and isophorone diisocyanate, and epoxy-based crosslinking agents such as 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane can be very suitably used. The content of the crosslinking agent is, for example, about 0.05 to 2 parts by weight per 100 parts by weight of the total monomer component forming the acrylic polymer.
[0162] For the above adhesive, when used in applications requiring heat resistance, curability in the presence of oxygen, and dimensional stability, it is preferable to contain an epoxy resin as the curable compound. Additionally, when used in applications requiring fast curability, it is preferable to contain an acrylic resin as the curable compound.
[0163] The above adhesive comprises the silicon compound and the curable compound, and since the silicon compound has a high concentration of silanol groups, it can exhibit excellent adhesive strength even at a low concentration. The content of the silicon compound in the above adhesive is, for example, 0.01 to 40 parts by weight, preferably 0.03 to 20 parts by weight, particularly preferably 0.05 to 10 parts by weight, and most preferably 0.1 to 5 parts by weight, per 100 parts by weight of the curable compound (preferably, epoxy resin or acrylic resin).
[0164] The adhesive may contain other components in addition to the silicon compound and the curable compound. Examples of other components include water, solvents, fillers, etc. Examples of solvents may include the same solvents that may be contained in the silane coupling agent described above.
[0165] In the case of bonding two inorganic materials, conventionally, the bonding surfaces of the two inorganic materials are modified in advance using a silane coupling agent, etc., and then bonded using an adhesive. However, when using the adhesive of the present disclosure, the adhesive of the present disclosure is applied directly to one bonding surface of the two inorganic materials, and then the two inorganic materials are bonded. Since the silanol group of the silicon compound included in the adhesive forms a Si-O-Si bond with the hydroxyl group on the surface of the inorganic material, and at the same time the reactive group with organic material in the silicon compound reacts with the adhesive, the two inorganic materials can be firmly bonded in an extremely simple manner.
[0166] In addition, the adhesive may include the silicon compound and the curable compound, and may be a one-component adhesive formed by mixing them in advance, or a two-component adhesive in which they are stored separately and mixed at the time of use. Among these, in the present disclosure, it is preferable to use it as a one-component adhesive due to its excellent workability. Since the adhesive contains a silicon compound with excellent storage stability, it can suppress gelation over a long period of time even when used as a one-component adhesive, allowing for stable storage.
[0167] [3D Laminate]
[0168] The three-dimensional laminate of the present disclosure has a configuration in which wafers and wafers, chips and chips, or wafers and chips are laminated through the adhesive (specifically, a cured product of the adhesive).
[0169] Among the above three-dimensional laminates, the structure in which wafers are stacked can be manufactured, for example, by the following (1) or (2).
[0170] 1: When using a one-component adhesive or a mixture of two-component adhesives as the adhesive, the adhesive is applied to the bonding surface of one wafer to bond the wafers, and then the adhesive is cured.
[0171] 2: When using a two-component adhesive, a first component containing a silicon compound is applied to the bonding surfaces of both wafers, and then the wafers are bonded with a second component containing a permanent adhesive, and then the permanent adhesive is cured.
[0172] Curing of the adhesive can be performed by a method depending on the type of adhesive. For example, when using a UV-curing adhesive, it can be cured by irradiating with ultraviolet light, and when using a thermosetting adhesive, it can be cured by performing a heat treatment.
[0173] Among the above three-dimensional laminates, a structure in which chips and chips or wafers and chips are stacked can also be manufactured by a method based on the above method.
[0174] A process is performed in which a through electrode (e.g., TSV) is formed in the above three-dimensional laminate, and then the laminate is diced to form a new one, mounted on a wiring board to bond the electrode, and then encapsulated with a resin or the like.
[0175] [Semiconductor Devices]
[0176] The semiconductor device of the present disclosure is characterized by having the above-described three-dimensional stack. Examples of the semiconductor device of the present disclosure include mobile devices such as smartphones and tablets, servers, workstations, computers for vehicles, personal computers, communication devices, imaging devices, image display devices, etc.
[0177] Since the semiconductor device of the present disclosure has the above-described three-dimensional stack, it can respond to high density, high speed, and low power consumption.
[0178] The foregoing description of each component of the present disclosure and combinations thereof is merely an example, and components may be appropriately added, omitted, substituted, or modified without departing from the well-known principles of the present disclosure. Furthermore, the present disclosure is not limited by embodiments but is limited only by the description in the claims.
[0179] Examples
[0180] The present disclosure will be explained more specifically below by way of examples, but the present disclosure is not limited by these examples.
[0181] Example 1 (Preparation of silane coupling agent)
[0182] 3-glycidoxypropyl triethoxysilane and a 0.003 wt% aqueous acetic acid solution were added to a reaction vessel and heated at 70°C for 3 hours under conditions of pH 4 and 6 equal parts water. As a result, hydrolysis and polycondensation reactions proceeded with a conversion rate of 100%.
[0183] After that, the heat treatment was stopped, and 39.9 g of ethanol was added to 5 g of the obtained crude product to obtain a silane coupling agent (1) (viscosity at 25℃, rotation speed 0.5 rpm: <5 mPa·s).
[0184] In addition, when the evaporation rate of butyl acetate of ethanol is set to 100, the evaporation rate is 203, and the SP value at 25℃ is 12.7.
[0185] The weight ratio of compound (I) / compound (II) in the silane coupling agent (1) was determined by GPC measurement.
[0186] In addition, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the silicon compound in the silane coupling agent (1) in the standard polystyrene equivalent were obtained by GPC measurement.
[0187] In addition, GPC measurements were performed using the following device under the following conditions.
[0188] Measuring device: Product name "LC-20AD", Product of Shimadzu Corporation
[0189] Column: Shodex KF-801 x 2 + KF-802 x 1 + KF-803 x 1 (Product of Showa Denko KK)
[0190] Measured temperature: 40℃
[0191] Eluent: THF
[0192] Sample concentration 0.1~0.2 wt%
[0193] Flow rate: 1 mL / min
[0194] Detector: UV-VIS detector (Product name "SPD-20A", manufactured by Shimadzu Seisakusho Co., Ltd.)
[0195] Example 2 (Preparation of silane coupling agent)
[0196] A silane coupling agent (2) was obtained in the same manner as in Example 1, except that PGMEA was used instead of ethanol.
[0197] In addition, the evaporation rate of PGMEA when the evaporation rate of butyl acetate is set to 100 is 19, and the SP value at 25℃ is 8.7.
[0198] Example 3 (Preparation of silane coupling agent)
[0199] A silane coupling agent (3) was obtained in the same manner as in Example 1, except that the heating temperature was changed to 50°C and the pH of the aqueous acetic acid solution was changed to 2.67. The silane coupling agent (3) was applied to Si-NMR measurement. The results are shown in FIG. 4(A).
[0200] Example 4 (Preparation of silane coupling agent)
[0201] A silane coupling agent (4) was obtained in the same manner as in Example 1, except that the heating temperature was changed to 50℃, the heating time to 4 hours, and the pH of the aqueous acetic acid solution to 3.
[0202] Example 5 (Preparation of silane coupling agent)
[0203] Except for changing the heating temperature to 50℃ and the heating time to 6 hours, the procedure was the same as in Example 1. As a result, the hydrolysis reaction and polycondensation reaction proceeded with a conversion rate of 90%, and a silane coupling agent (5) was obtained.
[0204] Example 6 (Preparation of silane coupling agent)
[0205] Except for changing the amount of water to 3 eq and the heating time to 11 hours, the procedure was the same as in Example 1. As a result, the hydrolysis reaction and polycondensation reaction proceeded with a conversion rate of 78%, and a silane coupling agent (6) was obtained.
[0206] Example 7 (Preparation of Silane Coupling Agent)
[0207] Except for changing the amount of water to 9 eq, the procedure was the same as in Example 1. As a result, the hydrolysis reaction and polycondensation reaction proceeded with a conversion rate of 100%, and a silane coupling agent (7) was obtained.
[0208] Example 8 (Preparation of silane coupling agent)
[0209] 100 parts by weight of 3-glycidoxypropyl triethoxysilane and 20 parts by weight of a 10% by weight aqueous acetic acid solution were added to a reaction vessel and stirred at 50°C for 6 hours. After that, the reaction mixture was concentrated at 40°C for 2 hours and PGMEA was added to obtain a silane coupling agent (8).
[0210] Example 9
[0211] 100 parts by weight of 3-glycidoxypropyl triethoxysilane and 20 parts by weight of a 10% by weight aqueous acetic acid solution were added to a reaction vessel and stirred at 50°C for 6 hours. After that, PGMEA was added to the reaction solution to obtain a silane coupling agent (9).
[0212] Comparative Example 1 (Preparation of silane coupling agent)
[0213] A silane coupling agent (10) was obtained in the same manner as in Example 1, except that ethanol was added from the beginning of the reaction instead of after the reaction was finished.
[0214] That is, 3-glycidoxypropyl triethoxysilane, an aqueous solution of acetic acid, and ethanol were added to a reaction vessel, and the reaction vessel was heated at 70°C for 3 hours under conditions of pH 4, 6 eq of water, and 6 eq of ethanol.
[0215] After that, the heat treatment was stopped, and 36.9 g of ethanol was added to 5 g of the obtained crude product to obtain a silane coupling agent (10).
[0216] Comparative Example 2
[0217] 50 parts by weight of 3-glycidoxypropyl triethoxysilane, 50 parts by weight of PGMEA, and 2 parts by weight of water were added to a reaction vessel. The pH inside the reaction vessel was 5. The reaction vessel was heated at 45°C for 30 days.
[0218] After that, the heat treatment was stopped to obtain a silane coupling agent (11).
[0219] A silane coupling agent (11) was applied to the Si-NMR measurement. The results are shown in Fig. 4(B).
[0220] Storage stability of the silane coupling agents obtained in Examples 1 to 9 and Comparative Examples 1 and 2 was evaluated by the following method.
[0221] That is, an experiment was conducted in which a silane coupling agent was left standing at room temperature, and the increase in weight-average molecular weight from immediately after the start of the experiment to 40 days later was measured to evaluate storage stability according to the following criteria.
[0222] metewand
[0223] ◎ (Very Good): After 40 days from the start of the experiment, no white precipitate is formed, and the increase in weight-average molecular weight is 100 or less.
[0224] ○ (Good): After 40 days from the start of the experiment, no white precipitate is formed, and the increase in weight-average molecular weight exceeds 100 and is 500 or less.
[0225] △ (Slightly Poor): After 40 days from the start of the experiment, no white precipitate is formed, but the increase in weight-average molecular weight exceeds 500.
[0226] × (Poor): White precipitate formed
[0227] The above results are summarized in Table 1 below.
[0228]
[0229] In addition, the storage stability of the silane coupling agents obtained in Examples 1 and 2 at 5°C or 40°C was evaluated by the following method.
[0230] Experiments were conducted in which the silane coupling agent was left standing at 5°C or 40°C, and the increase in weight-average molecular weight was measured from immediately after the start of the experiment until 40 days later. The results are shown in Figure 5.
[0231] Examples 10–18, Comparative Examples 3, 4
[0232] A two-component adhesive was obtained comprising a silane coupling agent obtained in Examples 1 to 9 and Comparative Examples 1 and 2 (the concentration of the silicon compound in the silane coupling agent was changed as described in Table 2 below by adding the solvent described in Table 2 below) and a curable composition (1) obtained in Preparation Example 1 below.
[0233] Preparation Example 1
[0234] 161.5 mmol (39.79 g) of 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 9 mmol (1.69 g) of phenyltrimethoxysilane, and 165.9 g of acetone were added to a 300 mL flask (reaction vessel) equipped with a thermometer, a stirring device, a reflux condenser, and a nitrogen inlet tube under a nitrogen stream, and the temperature was raised to 50°C. To the mixture thus obtained, 4.70 g of a 5% aqueous potassium carbonate solution (1.7 mmol as potassium carbonate) was added dropwise over 5 minutes, and then 1700 mmol (30.60 g) of water was added dropwise over 20 minutes. Additionally, no significant temperature rise occurred during the dropwise addition. Afterward, the polycondensation reaction was carried out at 50°C under a nitrogen stream for 4 hours.
[0235] When the product in the reaction solution after the polycondensation reaction was analyzed, the number average molecular weight was 1900 and the molecular weight dispersion was 1.5. of the above product 29The ratio of T2 bodies to T3 bodies [T3 bodies / T2 bodies] calculated from the Si-NMR spectrum was 10.3.
[0236] After that, the reaction solution was cooled, washed with water until the lower layer became neutral, and the upper layer was taken off. Then, the solvent was distilled off from the upper layer under conditions of 1 mmHg and 40°C until the solvent content became 25% by weight, thereby obtaining a colorless, transparent liquid product (epoxy group-containing polyorganosilsesquioxane).
[0237] A curable composition (1) was obtained by mixing 100 parts by weight of the obtained epoxy group-containing polyorganosilsesquioxane, 50 parts by weight of propylene glycol monomethyl ether acetate, 0.1 parts by weight of the product name "SAN-AID SI-150L" (product of SANSHIN CHEMICAL INDUSTRY CO., LTD., antimony-based sulfonium salt), and 0.005 parts by weight of the product name "SAN-AID SI Auxiliary" (product of SANSHIN CHEMICAL INDUSTRY CO., LTD., (4-hydroxyphenyl)dimethylsulfonium methylsulfite).
[0238] <Adhesion Evaluation>
[0239] The adhesive properties of the two-component adhesives obtained in the examples and comparative examples were evaluated by the following method.
[0240] A silane coupling agent with a concentration adjusted with a diluent was applied by spin coating to one side of a glass plate (4 inch, manufactured by SCHOTT Japan Co., Ltd.) and heated at 100°C for 15 minutes to obtain a silane coupling agent layer (thickness: 0.01 μm). Then, a curable composition (1) was applied by spin coating to the surface of the obtained silane coupling agent layer to produce a curable composition layer (thickness: 2.5 μm), thereby obtaining a laminate having the composition of glass plate / silane coupling agent layer / curable composition layer.
[0241] The laminate obtained above was heated at 150°C for 30 minutes and then heated at 170°C for 30 minutes, and used as a sample. The obtained samples (5 samples for each sample) were evaluated by a cross-cut tape test in accordance with JIS K5400-8.5.
[0242] ○ (Excellent Adhesion): No peeling in all 5 samples
[0243] △ (Good adhesion): Delamination on 1~2 samples
[0244] × (Poor adhesion): Delamination in 3 or more samples
[0245] The results are summarized and presented in Table 2 below.
[0246]
[0247] Example 19
[0248] The silane coupling agent (1) obtained in Example 1 and the curable composition (1) obtained in Preparation Example 1 were mixed and dissolved while changing the amount of silane coupling agent added so that the concentration of the silicon compound in the silane coupling agent relative to the curable composition (1) was as described in Table 3 below, thereby obtaining 10 g of one-component adhesive.
[0249] Comparative Example 5
[0250] A one-component adhesive was obtained by doing the same as in Example 19, except that a silane coupling agent (11) was used instead of a silane coupling agent (1).
[0251] <Adhesion Evaluation>
[0252] For the one-component adhesives obtained in Example 19 and Comparative Example 5, the adhesiveness was evaluated by the following method.
[0253] The obtained one-component adhesive was applied to one side of a glass plate (4 inch, manufactured by SCHOTT Japan Co., Ltd.) by spin coating, heated at 80°C for 4 minutes, followed by heating at 100°C for 2 minutes to remove residual solvent. Subsequently, heated at 150°C for 30 minutes, followed by heating at 170°C for 30 minutes to obtain a laminate having a composition of glass plate / adhesive layer.
[0254] The laminates obtained above (number of samples: 5) were evaluated by a cross-cut tape test in accordance with JIS K5400-8.5. In addition, the evaluation criteria are the same as those for the evaluation of the adhesion of two-component adhesives.
[0255] The results are summarized in Table 3 below.
[0256] Example 19 Comparative Example 5 Silicon compound concentration (wt%) 1 ○ × 0.1 ○ × 0.04 ○ ×
[0257] As summarized above, the configuration of the present disclosure and variations thereof are appended below.
[0258] [1] A silane coupling agent containing the following silicon compound and water, wherein the concentration of the silicon compound is 0.01 to 10 weight%.
[0259] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0260] [2] A silane coupling agent containing the following silicon compound and water, wherein the concentration of the silicon compound is 0.01 to 10 weight%.
[0261] Silicon compound: includes compound (I) represented by formula (1) and compound represented by formula (3), wherein the ratio of the content of compound (II) among the compounds represented by formula (3) and compound (I) having a weight average molecular weight of 200 to 10000 based on standard polystyrene conversion [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0262] [3] A silane coupling agent described in [1] or [2], wherein the content of the compound having a weight average molecular weight of less than 200 in standard polystyrene is 30% by weight or less of the total amount of silicon compounds included in the silane coupling agent.
[0263] [4] A silane coupling agent described in [1] or [2], wherein the content of the compound having a weight average molecular weight of 10,000 by standard polystyrene conversion is 30% by weight or less of the total amount of silicon compounds included in the silane coupling agent.
[0264] [5] A polycondensate of compound (I) (or a compound represented by formula (3)), wherein the total content of a compound with a weight average molecular weight of less than 200 in standard polystyrene equivalent and a compound with a weight average molecular weight of more than 10000 in standard polystyrene equivalent is 30% by weight or less of the total amount of silicon compounds included in the silane coupling agent, as described in [1] or [2].
[0265] [6] A silane coupling agent described in any one of [1] to [5], wherein the content of the compound represented by formula (2) is 50% by weight or less of the total amount of silicon compounds included in the silane coupling agent.
[0266] [7] A silane coupling agent with a pH of 4 or less, as described in any one of [1] to [6].
[0267] [8] Additionally, a silane coupling agent described in any one of [1] to [7] containing a solvent having the following characteristics.
[0268] Solvent: The evaporation rate of butyl acetate is 10 to 400 when the evaporation rate of butyl acetate is set to 100.
[0269] [9] Additionally, a silane coupling agent described in any one of [1] to [7] containing a solvent having the following characteristics.
[0270] Solvent: When the evaporation rate of butyl acetate is set to 100, the evaporation rate is 10 to 400, and the SP value at 25°C is 6 to 15.
[0271]
[10] Additionally, a silane coupling agent containing an aliphatic alcohol, as described in any one of [1] to [7].
[0272]
[11] Additionally, a silane coupling agent containing a monovalent aliphatic alcohol, as described in any one of [1] to [7].
[0273]
[12] Additionally, C of 1 2-6 A silane coupling agent containing an aliphatic alcohol, as described in any one of [1] to [7].
[0274]
[13] Additionally, a silane coupling agent containing ethanol, as described in any one of [1] to [7].
[0275]
[14] A silane coupling agent described in any one of [1] to
[13] , having a viscosity of 1 to 300 mPa·s at 25℃ and a rotation speed of 0.5 rpm.
[0276]
[15] A silane coupling agent described in any one of [1] to
[14] , having a weight average molecular weight increase value of 500 or less when stored at 25°C for 30 days in standard polystyrene equivalent.
[0277]
[16] A silane coupling agent described in any one of [1] to
[15] , having a weight average molecular weight increase of 2000 or less when stored at 40°C for 30 days in standard polystyrene equivalent.
[0278]
[17] A surface modifier, a silane coupling agent as described in any one of [1] to
[16] .
[0279]
[18] A method for manufacturing a silane coupling agent comprising: a process of hydrolyzing a compound represented by formula (2) to obtain a compound represented by formula (1) under conditions of pH 4 or lower, and at the same time, in the absence of an organic solvent, or even if an organic solvent is present, in the case where the organic solvent is present, in the case where the organic solvent content is 0.7 parts by weight or less per 1 part by weight of the compound represented by formula (2); and a process of obtaining a silane coupling agent described in any one of [1] to
[17] by applying the obtained compound represented by formula (1) to a polycondensation reaction.
[0280]
[19] An adhesive comprising the following silicon compound and a curable compound.
[0281] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0282]
[20] The adhesive described in
[19] , wherein the content of the silicon compound is 0.01 to 40 parts by weight per 100 parts by weight of the curable compound.
[0283]
[21] An adhesive containing the following silicon compound and an epoxy group-containing polyorganosilsesquioxane.
[0284] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0285]
[22] The adhesive described in
[21] , wherein the content of the silicon compound is 0.01 to 40 parts by weight per 100 parts by weight of the epoxy group-containing polyorganosilsesquioxane.
[0286]
[23] A three-dimensional laminate having a configuration in which wafers and wafers, chips and chips, or wafers and chips are laminated through an adhesive described in any one of
[19] to
[22] .
[0287]
[24] A semiconductor device having the three-dimensional stack described in
[23] .
[0288]
[25] A method for manufacturing a three-dimensional laminate by using an adhesive containing the following silicon compound and a curable compound to bond wafers and wafers, chips and chips, or wafers and chips together.
[0289] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0290]
[26] Use of a silane coupling agent as a surface modifier in any one of [1]~
[17] .
[0291]
[27] Use of a composition containing the following silicon compound and curable compound in an adhesive.
[0292] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0293]
[28] Use in an adhesive of a composition comprising the following silicon compound and a curable compound, wherein the silicon compound content is 0.01 to 40 parts by weight per 100 parts by weight of the curable compound.
[0294] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0295]
[29] Use of a composition containing the following silicon compound and an epoxy group-containing polyorganosilsesquioxane in adhesives.
[0296] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0297]
[30] Use in an adhesive of a composition comprising the following silicon compound and an epoxy group-containing polyorganosilsesquioxane, wherein the silicon compound content is 0.01 to 40 parts by weight per 100 parts by weight of the epoxy group-containing polyorganosilsesquioxane.
[0298] Silicon compound: comprises compound (I) represented by formula (1) and its polycondensate, wherein the ratio of the content of compound (I) and compound (II) having a weight average molecular weight of 200 to 10000 in the polycondensate of compound (I) [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5.
[0299] Industrial applicability
[0300] The silane coupling agent of the present disclosure can firmly bond inorganic and organic materials even at low concentrations. In addition, it has excellent storage stability.
[0301] When an adhesive containing the silane coupling agent of the present disclosure is used in semiconductor chip stacking technologies such as the WOW method, COW method, or COC method, extremely fine and thinned wafers or chips can be strongly bonded and fixed, and a three-dimensional stack can be manufactured with high yield.
Claims
Claim 1 A silane coupling agent comprising the following silicon compound and water, wherein the concentration of the silicon compound is 0.01 to 10 wt%. Silicon compound: comprising a compound (I) represented by the following formula (1) and its polycondensate obtained by hydrolyzing a compound represented by the following formula (2) under conditions where the pH is 4 or lower, the organic solvent is absent, or even if an organic solvent is present, the organic solvent content is 0.2 wt% or less per 1 wt of the compound represented by the following formula (2), and the amount of water used is 3 to 12 moles per 1 mole of the compound represented by the following formula (2), wherein the ratio of the content of compound (I) and compound (II) among the polycondensates of compound (I), wherein the weight average molecular weight calculated by standard polystyrene is 200 to 10000 [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5. [Chem 1] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter)[Chem 2] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter, and OR 1 ~OR 3 It is identical or different and exhibits a hydrolytic group) Claim 2 A silane coupling agent having a pH of 4 or less, as described in claim 1. Claim 3 A silane coupling agent according to claim 1 or 2, additionally containing a solvent having the following characteristics. Solvent: The evaporation rate of butyl acetate is 10 to 400 when the evaporation rate of butyl acetate is 100. Claim 4 A silane coupling agent according to claim 1 or 2, additionally comprising a solvent having the following characteristics: Solvent: The evaporation rate of butyl acetate is 10 to 400 when the evaporation rate of butyl acetate is 100, and the SP value at 25°C is 6 to 15. Claim 5 In paragraph 1 or 2, a silane coupling agent which is a surface modifier. Claim 6 A silane coupling agent according to claim 1 or 2, wherein the ratio of the content of compound (I) and compound (II) [compound (I) / compound (II); weight ratio] of the silicon compound is 10 / 90 to 95 / 5. Claim 7 A silane coupling agent according to claim 1 or 2, wherein the weight average molecular weight of the silicon compound converted to standard polystyrene is 150 to 510. Claim 8 Under conditions where the pH is 4 or lower, there is no organic solvent, or even if an organic solvent is present, the content of the organic solvent is 0.2 parts by weight or less per 1 part by weight of the compound represented by the following formula (2), and the amount of water used is 3 to 12 moles per 1 mole of the compound represented by the following formula (2), the following formula (2) [Formula 3] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter, and OR 1 ~OR 3 Hydrolyze a compound represented by (which is identical or different and represents a hydrolytic group) to form the following formula (1) [Chem 4] A method for manufacturing a silane coupling agent comprising a process of obtaining a compound represented by (wherein Y is the same as above), and a process of obtaining a silane coupling agent described in claim 1 or 2 by applying the obtained compound represented by formula (1) to a polycondensation reaction. Claim 9 An adhesive comprising the following silicon compound and a curable compound. Silicon compound: comprises a compound (I) represented by the following formula (1) and its polycondensate obtained by hydrolyzing a compound represented by the following formula (2) under conditions where the pH is 4 or lower, the organic solvent is absent, or even if an organic solvent is present, the organic solvent content is 0.2 parts by weight or less per 1 part by weight of the compound represented by the following formula (2), and the amount of water used is 3 to 12 moles per 1 mole of the compound represented by the following formula (2), wherein the ratio of the content of compound (I) and compound (II) among the polycondensates of compound (I), wherein the weight average molecular weight calculated by standard polystyrene is 200 to 10000 [compound (I) / compound (II); weight ratio] is 1 / 99 to 95 / 5. [Chemical 5] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter)[Chem 6] (In the formula, Y represents a hydrocarbon group having 1 to 10 carbon atoms containing a reactive group with organic matter, and OR 1 ~OR 3 It is identical or different and exhibits a hydrolytic group) Claim 10 An adhesive according to claim 9, wherein the content of the silicon compound is 0.01 to 40 parts by weight per 100 parts by weight of the curable compound. Claim 11 A three-dimensional laminate having a configuration in which wafers and wafers, chips and chips, or wafers and chips are laminated through the adhesive described in claim 9. Claim 12 A semiconductor device having a three-dimensional stack as described in claim 11.
Citation Information
Patent Citations
Heat-conducting organic silicon adhesive, cured product thereof and LED element
CN109880583A
Aqueous dispersion
JP2003003030A
Gas barrier film and method for producing same
KR1020160140824A
Anti-corrosion coating film structure, metallic member equipped with same, Anti-corrosion treatment method, and surface-treating agent
WO2015011778A1
Silane oligomer composition
JP1998251516A
